Makoons - Erdrich, Louise (Harper, 2018)
Living with their Ojibwe family on the Great Plains of Dakota Territory in 1866, twin brothers Makoons and Chickadee must learn to become buffalo hunters, but Makoons has a vision that foretells great challenges that his family may not be able to overcome.